2008
DOI: 10.1177/112067210801800617
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Characteristics, and Risk Factors of Late Recurrence of Retinal Detachment

Abstract: LRRD were rare. Most of them were due to a retinal break. This break can be a new break, or reopened break especially after removal of scleral buckle material. Vitreous traction, at the vitreous base, seemed to be the cause of these breaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…They found 10 cases that developed a late recurrence RRD, of which nine eyes were repaired by SB and one with pneumatic retinopexy, with a success rate of reattachment of 63%, but two cases developed a second late recurrence of retinal detachment at 85 and 100 months. Zhioua et al 12 analyzed 445 operated eyes for RRD, identifying nine eyes with a late recurrence RRD, of these, six eyes had SB and three eyes had vitrectomy with silicone oil injection and then silicone oil removal. The series were reported more than 15 years ago when SB was more commonly used to repair RRD; this has now changed and currently vitrectomy alone is the most common technique.…”
Section: Discussionmentioning
confidence: 99%
“…They found 10 cases that developed a late recurrence RRD, of which nine eyes were repaired by SB and one with pneumatic retinopexy, with a success rate of reattachment of 63%, but two cases developed a second late recurrence of retinal detachment at 85 and 100 months. Zhioua et al 12 analyzed 445 operated eyes for RRD, identifying nine eyes with a late recurrence RRD, of these, six eyes had SB and three eyes had vitrectomy with silicone oil injection and then silicone oil removal. The series were reported more than 15 years ago when SB was more commonly used to repair RRD; this has now changed and currently vitrectomy alone is the most common technique.…”
Section: Discussionmentioning
confidence: 99%
“…In our cases, 2 eyes had high myopia with an AL >26.5 mm. Zhioua et al [13] reported the late rRRDs after SB (6 eyes) or PPV (3 eyes) were statistically independent of myopia. Our cases were initially treated by PPV and might have different characteristics.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Majority of the studies quote PVR ≥ Grade C, anterior and inferior PVR to be associated with a higher risk re-RD. [ 6 7 8 9 10 11 12 13 14 15 16 17 19 20 21 22 26 ] It was previously reported that 86% of eyes with re-RD after vitrectomy have a component of anterior PVR[ 27 ] and eyes with anterior PVR have poorer surgical prognosis than those with posterior PVR. [ 28 ]…”
Section: Risk Factors Relating To Redetachmentmentioning
confidence: 99%
“…The second most common cause of redetachment was related to retinal breaks. Large breaks more than three disk diameters,[ 6 8 ] formation of new breaks or missed breaks[ 6 7 8 9 13 14 15 19 21 22 ] or ineffective closure of preexisting breaks either by improper positioning of the scleral buckle (SB) or by inadequate chorioretinal adhesion,[ 12 13 21 26 ] reopening of an old break[ 19 ] and reopened macular hole[ 22 ] lead to redetachment.…”
Section: Risk Factors Relating To Redetachmentmentioning
confidence: 99%